The Unfinished Business of Social Justice in Christian Higher Education. Issue 5 (20th October 2019) - Luna De La Rosa, Mari; Jun, Alexander
Abstract: In this essay, we contend that there is much unfinished business ahead for Christian higher education. Our argument is grounded in the cumulative impact of long-standing frameworks and an expanding knowledge base on diversity and social justice in higher education. In 2013, we edited a special volume of this journal calling for focused work on faith, diversity, and social justice within Christian higher education. Since then, we feel heavily influenced by racialized events in the United States and our concern as educators regarding the role and responsibility of Christian higher education in educating its students. The purpose of the article is to challenge and extend the conversation on diversity and social justice in Christian higher education. To that end, we suggest questions that Christian higher education leaders should be asking of themselves. We emphasize how Christian higher education can take the lead in advancing social justice as part of its mission. We explore definitions and old paradigms and discuss the significance of current events and cultural thinking. We then outline actionable institutional frameworks and initiatives that can move Christian higher education forward.